Exploring Circular Economy with an Engineered Approach for Waste to Wealth - Palkar, Ritesh Ramesh (Dunakavics, 2023)
The ecosystem is facing a significant burden as the population continues to grow rapidly. This has led to a tremendous rise in demands, which in turn has resulted in the generation of waste through various means, primarily due to the adoption of a linear economy approach. Industrialization emerged as an obvious response to the perceived scarcity of natural resources. However, this approach led to a one-way system, resulting in the accumulation of undesirable materials that we now have to confront. Although nature has taught us the value of a circular economy, mankind opted for a linear economy model to improve living standards. Today, we are all concerned about the unpredictable environmental changes and their potential consequences. To address these inevitable challenges, a concrete and comprehensive plan must be presented and implemented across all sectors. Creating awareness is a crucial step in promoting the adoption of a circular economy approach. In light of this, the author wishes to showcase several case studies where what is commonly considered waste is being transformed into valuable resources. This article focuses on areas such as solid waste management and wastewater treatment. It emphasizes the importance of carefully managing industrial waste, which can be harnessed as an energy source. This approach ultimately aims to achieve zero waste generation and zero liquid discharge.